Intravenous paracetamol and patent ductus arteriosus closure in preterm infants - Rizky Adriansyah; Nikmah S. Idris; Mulyadi M. Djer; Sukman T. Putra; Rinawati Rohsiswatmo (Indonesian Pediatric Society, 2017)
Background Indomethacin and ibuprofen are the drugs of choice for closure of patent ductus arteriosus (PDA) in preterm infants. However, intravenous preparations are of limited availability in Indonesia. Circumstantial evidence has shown that intravenous paracetamol may be an alternative therapy for PDA closure in premature infants.Objective To evaluate the effect of intravenous paracetamol on PDA closure in preterm infants.Methods A before-and-after study was conducted between May and August 2014 in Cipto Mangunkusumo General Hospital, Jakarta in preterm infants with hemodynamically significant PDAs, as established by echocardiography using the following criteria: duct diameter >1.4 mm/kg, left atrium to aorta ratio >1.4, and mean velocity in the left pulmonary artery >0.42 m/s or mean diastolic velocity in the left pulmonary artery >0.2 m/s. Subjects, aged 2 and 7 days, received intravenous paracetamol (15 mg/kg every six hours) for 3 days. Paired T-test was used to compare pre-intervention PDA diameter to those assessed at 24 hours after the intervention and at 14 days of life.Results Twenty-nine subjects had a mean gestational age of 30.8 weeks and mean birth weight of 1,347 grams. Nineteen (65.5%) patients had closed PDAs at the day 14 evaluation, 1 experienced PDA reopening, and 9 had failed PDA closure. No liver toxicity was identified. Mean duct diameters before, 24 hours after the intervention, and at 14 days of life were 3.0, 0.9, and 0.6 mm, respectively (P<0.0001).Conclusion Intravenous paracetamol seems to be reasonably effective for PDA closure in preterm infants.